Reducing TRPC1 Expression through Liposome-Mediated siRNA Delivery Markedly Attenuates Hypoxia-Induced Pulmonary Arterial Hypertension in a Murine Model - Cheuk-Kwan Sun; Yen-Yi Zhen; Hung-I Lu; Pei-Hsun Sung; Li-Teh Chang; Tzu-Hsien Tsai; Jiunn-Jye Sheu; Yung-Lung Chen; Sarah Chua; Hsueh-Wen Chang; Yi-Ling Chen; Fan-Yen Lee; et al. (Hindawi Limited, 2014)
We tested the hypothesis that Lipofectamine siRNA delivery to deplete transient receptor potential cation channel (TRPC) 1 protein expression can suppress hypoxia-induced pulmonary arterial hypertension (PAH) in mice. Adult male C57BL/6 mice were equally divided into group 1 (normal controls), group 2 (hypoxia), and group 3 (hypoxia + siRNA TRPC1). By day 28, right ventricular systolic pressure (RVSP), number of muscularized arteries, right ventricle (RV), and lung weights were increased in group 2 than in group 1 and reduced in group 3 compared with group 2. Pulmonary crowded score showed similar pattern, whereas number of alveolar sacs exhibited an opposite pattern compared to that of RVSP in all groups. Protein expressions of TRPCs, HIF-1α, Ku-70, apoptosis, and fibrosis and pulmonary mRNA expressions of inflammatory markers were similar pattern, whereas protein expressions of antifibrosis and VEGF were opposite to the pattern of RVSP. Cellular markers of pulmonary DNA damage, repair, and smooth muscle proliferation exhibited a pattern similar to that of RVSP. The mRNA expressions of proapoptotic and hypertrophy biomarkers displayed a similar pattern, whereas sarcomere length showed an opposite pattern compared to that of RVSP in all groups. Lipofectamine siRNA delivery effectively reduced TRPC1 expression, thereby attenuating PAH-associated RV and pulmonary arteriolar remodeling.